ANALISIS KEMAMPUAN BERPIKIR KREATIF PESERTA DIDIK DALAM MENYELESAIKAN MASALAH MATEMATIKA BERBASIS HOTS - Restu Azahrah Fatmah; Nugraheni, Esti Ambar (Universitas Cokroaminoto Palopo, 2022)
This study aims to determine the creative thinking abilities students of SMPIT Raflesia in class VIII in solving problems based on higher order thinking skills. The method used in this research is a qualitative research method with a case study approach. The results of this study indicate that overall creative thinking skills in solving HOTS-based questions at SMPIT Raflesia are still very low. Students with high categories can achieve 4 indicators of creative thinking namely: fluency, flexibility, originality and elaboration. Students in the low category can achieve 3 indicators of creative thinking namely: fluency, originality and elaboration. Meanwhile, students with low category levels can achieve one indicator of creative thinking namely: fluency. Relatively, the creative thinking ability of students is still low with an average percentage of 39% for all indicators.